Application of Warm Cinnamon Compresses to Reduce Pain Scale in Older Adults with Gout Arthritis in the Simpang Periuk Health Center Working Area 2023 - Soewito, Bambang; Susmini, Susmini; Wijaya, Sapondra; Wibowo, Wahyu Dwi Ari; Martini, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Patients with Gout Arthritis often suffer from intense pain. While there's no one-size-fits-all cure for joint pain in older adults with this condition, there are various ways to ease the discomfort. Cinnamon compresses can help alleviate the symptoms. Compounds like eugenol and cinnamaldehyde in cinnamon create a warm feeling on the skin, calming inflammation by slowing down pain signals. This can help lower sensitivity to pain and make it easier to manage. The case study method used was a descriptive case study method, with two subjects of older ages with Gout Arthritis, using the format of assessment of family nursing care and evaluation of pain scales. Cinnamon compresses are carried out four times a week using 2 ml of cinnamon liquid, with 200cc of water, at a temperature of 40-450C, followed by compresses for 15-20 minutes using a washcloth. After applying cinnamon compresses four times a week, the study showed a decrease in pain intensity before and after the intervention was given to the two subjects. The Subject's pain intensity decreased from moderate to mild pain. The application of cinnamon compresses is effective in reducing the intensity of Gout Arthritis pain.